Maintenance, update and further development of EFSA's Chemical Hazards: OpenFoodTox 2.0. Issue 3 (27th March 2020) - Benfenati, Emilio; Carnesecchi, Edoardo; Roncaglioni, Alessandra; Baldin, Rossella; Ceriani, Lidia; Ciacci, Andrea; Kovarich, Simona; Sartori, Luca; Mostrag, Aleksandra; Magdziarz, Tomasz; Yang, Chihae
Abstract : The present document is a summary of the activities undertaken during the first year of the framework contract (OC/EFSA/SCER/2018/01) undertaken for the maintenance, update and further development of EFSA's chemical Hazards database "OpenFodTox 2.0". OpenFoodTox has been developed over the last 7 years to map and collect hazards data published inEFSA outputs for the risk assessment of chemicals in food and feed(i.eopinions, statements and conclusions). More specifically, the database holds summary data on identification of chemicals, document descriptors, hazard identification, and hazard characterisation. Within OpenFoodTox 2.0, the collection and entry of all hazard data assessed by EFSA scientific panels was performed according to the existing data modelwith the inclusion of PARAM codes. In parallel, OpenFoodToxdata model was further expanded to incorporate new properties in the database including physicochemical properties (OHT 1 to 23‐5), degradation and bioaccumulation (OHT 32 and 33), toxicokinetic data (OHT 58), intermediate effects (OHT 201), "New Approach methodologies (NAM)" as proposedby the European Chemicals Agency use and exposure information (OHT 301 to 306), as well as any other properties deemed relevant.Data for new substance properties have been collected from recent EFSA documents published in 2018 and 2019andwill be integrated in OpenFoodTox 2.0 in the new data model.Furthermore, preliminary results on new QSAR models are here presented as part of the design of an in silico integrative tool allowing description and prediction of hazard properties of chemicals within "OpenFoodTox 2.0".